Meiosis-specific distal cohesion site decoupled from the kinetochore - Bo Pan; Melania Bruno; Todd S. Macfarlan; Takashi Akera (Nature Communications)
Abstract Primary constriction of the M-phase chromosome serves as a marker for the kinetochore position. Underlying this observation is the concept that the kinetochore is spatially linked with the pericentromere where sister-chromatids are cohered. Here, we find an unconventional chromatid-cohesion pattern in Peromyscus oocytes, with sister chromatids cohered at a chromosome end, spatially separated from the kinetochore. This distal locus enriches cohesin protectors specifically during meiosis, and chromosomes with this additional cohesion site exhibit enhanced cohesin protection at anaphase I compared to those without it, implying an adaptive evolution to ensure cohesion during meiosis. The distal locus corresponds to an additional centromeric satellite block, located far from the satellite block building the kinetochore. Analyses on three Peromyscus species reveal that the internal satellite consistently assembles the kinetochore in mitosis and meiosis, whereas the distal satellite selectively enriches cohesin protectors in meiosis to promote cohesion. Our study demonstrates that cohesion regulation is flexible, controlling chromosome segregation in a cell-type dependent manner.